2019
DOI: 10.1159/000504173
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Differences in Platelet Inhibition Response to Prostaglandin E1

Abstract: <b><i>Background:</i></b> The mechanisms underlying neonatal platelets hyporesponsiveness are not fully understood. While previous studies have demonstrated developmental impairment of agonist-induced platelet activation, differences in inhibitory signaling pathways have been scarcely investigated. <b><i>Objective:</i></b> To compare neonatal and adult platelets with regard to inhibition of platelet reactivity by prostaglandin E1 (PGE<sub>1</sub>). &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Worthy of special note is GNAI2, the main member of the Gαi family expressed on platelets [41]. In fact, in line with the higher levels of GNAI2 in plasma exosomes from neonates, we previously found that the expression levels of the gene that encode this protein, GNAI2, are significantly higher in neonatal platelets than in adult platelets [13].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Worthy of special note is GNAI2, the main member of the Gαi family expressed on platelets [41]. In fact, in line with the higher levels of GNAI2 in plasma exosomes from neonates, we previously found that the expression levels of the gene that encode this protein, GNAI2, are significantly higher in neonatal platelets than in adult platelets [13].…”
Section: Discussionmentioning
confidence: 80%
“…Despite the poor reactivity of platelets during the fetal/neonatal life, compared with older children or adults, healthy full-term infants exhibit normal to increased primary hemostasis due to factors in neonatal blood that enhance the platelet vessel wall interaction (i.e., increased von Willebrand factor (vWF) levels and function, higher hematocrit levels or higher mean corpuscular volumes of erythrocytes) [1]. Thus, platelet hyporeactiveness during the first weeks of life is seen as part of an exceptional and well-balanced haemostatic system [1,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A side effect of PGE is inhibition of platelet function, especially in neonates, so tranexamic acid infusions were used to minimize blood loss. 4 The FiO 2 was decreased intraoperatively to optimize Qp:Qs balance. Intraoperatively, Twin B required substantial hemodynamic support while carefully preserving…”
Section: Discussionmentioning
confidence: 99%
“…Different mechanisms contribute to the reduced responses of neonatal platelets to various agonists: 1. the hyporesponsiveness to epinephrine is due to a marked reduction in the number of α2-adrenergic receptors, the binding sites for epinephrine, on the surface of neonatal platelets; 2. the decreased responsiveness to thrombin is related to reduced expression of the thrombin receptors PAR-1 and PAR-4 in neonatal platelets (16); 3. the decreased response to thromboxane results from reduced signaling downstream from the receptor (17); 4. the reduced responses to collagen and rhodocytin result from mildly reduced expression of GPVI and CLEC-2, respectively, coupled with an intracellular signaling defect evidenced by reduced Syk and PLCγ2 phosphorylation following stimulation (14). Recently, developmental differences have also been described in regard to platelet inhibitory pathways, specifically a hypersensitivity of neonatal platelets to the inhibitory effects of prostaglandin E1 (PGE 1 ) during ADP-and collagen-induced platelet aggregation, associated with a functional increase in the PGE 1 -cAMP-PKA axis (18).…”
Section: Developmental Differences In Hemostasis Platelet Counts and mentioning
confidence: 99%